Inhaled gases as novel neuroprotective therapies in the postcardiac arrest period. Issue 3 (June 2021) - Magliocca, Aurora; Fries, Michael
Abstract : Purpose of review: The purpose of this review is to summarize recent advances about inhaled gases as novel neuroprotective agents in the postcardiac arrest period. Recent findings: Inhaled gases, as nitric oxide (NO) and molecular hydrogen (H2 ), and noble gases as xenon (Xe) and argon (Ar) have shown neuroprotective properties after resuscitation. In experimental settings, the protective effect of these gases has been demonstrated in both in-vitro studies and animal models of cardiac arrest. They attenuate neuronal degeneration and improve neurological function after resuscitation acting on different pathophysiological pathways. Safety of both Xe and H2 after cardiac arrest has been reported in phase 1 clinical trials. A randomized phase 2 clinical trial showed the neuroprotective effects of Xe, combined with targeted temperature management. Xe inhalation for 24 h after resuscitation preserves white matter integrity as measured by fractional anisotropy of diffusion tensor MRI. Summary: Inhaled gases, as Xe, Ar, NO, and H2 have consistently shown neuroprotective effects in experimental studies. Ventilation with these gases appears to be well tolerated in pigs and in preliminary human trials. Results from phase 2 and 3 clinical trials are needed to assess their efficacy in the treatment of postcardiac arrest brain injury.